Transcutaneous auricular VNS applied to experimental pain: A paired behavioral and EEG study using thermonociceptive CO(2) laser - Dumoulin, Manon (PLoS One, 2021)
BACKGROUND: Transcutaneous auricular Vagal Nerve Stimulation (taVNS) is a non-invasive neurostimulation technique with potential analgesic effects. Several studies based on subjective behavioral responses suggest that taVNS modulates nociception differently with either pro-nociceptive or anti-nociceptive effects. OBJECTIVE: This study aimed to characterize how taVNS alters pain perception, by investigating its effects on event-related potentials (ERPs) elicited by different types of spinothalamic and lemniscal somatosensory stimuli, combined with quantitative sensory testing (detection threshold and intensity ratings). METHODS: We performed 3 experiments designed to study the time-dependent effects of taVNS and compare with standard cervical VNS (cVNS). In Experiment 1, we assessed the effects of taVNS after 3 hours of stimulation. In Experiment 2, we focused on the immediate effects of the duty cycle (OFF vs. ON phases). Experiments 1 and 2 included 22 and 15 healthy participants respectively. Both experiments consisted of a 2-day cross-over protocol, in which subjects received taVNS and sham stimulation sequentially. In addition, subjects received a set of nociceptive (thermonociceptive CO(2) laser, mechanical pinprick) and non-nociceptive (vibrotactile, cool) stimuli, for which we recorded detection thresholds, intensity of perception and ERPs. Finally, in Experiment 3, we tested 13 epileptic patients with an implanted cVNS by comparing OFF vs. ON cycles, using a similar experimental procedure. RESULTS: Neither taVNS nor cVNS appeared to modulate the cerebral and behavioral aspects of somatosensory perception. CONCLUSION: The potential effect of taVNS on nociception requires a cautious interpretation, as we found no objective change in behavioral and cerebral responses to spinothalamic and lemniscal somatosensory stimulations.